A2A adenosine receptors are involved in the reparative response of tendon cells to pulsed electromagnetic fields. - Alessandra Colombini; Carlotta Perucca Orfei; Fabrizio Vincenzi; Paola De Luca; Enrico Ragni; Marco Viganò; Stefania Setti; Katia Varani; Laura de Girolamo (PLoS ONE, 2020)
Tendinopathy is a degenerative disease in which inflammatory mediators have been found to be sometimes present. The interaction between inflammation and matrix remodeling in human tendon cells (TCs) is supported by the secretion of cytokines such as IL-1β, IL-6 and IL-33. In this context, it has been demonstrated that pulsed electromagnetic fields (PEMFs) were able to reduce inflammation and promote tendon marker synthesis. The aim of this study was to evaluate the anabolic and anti-inflammatory PEMF-mediated response on TCs in an in vitro model of inflammation. Moreover, since PEMFs enhance the anti-inflammatory efficacy of adenosine through the adenosine receptors (ARs), the study also focused on the role of A2AARs. Human TCs were exposed to PEMFs for 48 hours. After stimulation, A2AAR saturation binding experiments were performed. Along with 48 hours PEMF stimulation, TCs were treated with IL-1β and A2AAR agonist CGS-21680. IL-1Ra, IL-6, IL-8, IL-10, IL-33, VEGF, TGF-β1, PGE2 release and SCX, COL1A1, COL3A1, ADORA2A expression were quantified. PEMFs exerted A2AAR modulation on TCs and promoted COL3A1 upregulation and IL-33 secretion. In presence of IL-1β, TCs showed an upregulation of ADORA2A, SCX and COL3A1 expression and an increase of IL-6, IL-8, PGE2 and VEGF secretion. After PEMF and IL-1β exposure, IL-33 was upregulated, whereas IL-6, PGE2 and ADORA2A were downregulated. These findings demonstrated that A2AARs have a role in the promotion of the TC anabolic/reparative response to PEMFs and to IL-1β.